Biological mechanisms of invasiveness of Ambrosia artemisiifolia L. and innovative control approaches - Onipko, V.; Pospelov, S.; Pospelova, H.; Kovalenko, N. (Scientific Progress & Innovations, 2025)
The purpose of the review was to summarize current scientific approaches to studying the biological mechanisms of invasiveness of Ambrosia artemisiifolia L., to identify ecological and agroeconomic risks associated with its spread, and to analyze innovative strategies for controlling this dangerous weed. Ambrosia artemisiifolia L. is one of the most aggressive invasive species of the Asteraceae family, posing a significant threat to agroecosystems, natural biodiversity, and human health. Its spread under conditions of trade globalization and climate change has reached a large scale, emphasizing the need for interdisciplinary research on the bioecological characteristics of this species and the development of comprehensive control strategies. The high invasive potential of A. artemisiifolia is determined by a complex of adaptive traits: rapid initial growth, tolerance to various soil types and climatic conditions, a powerful root system, cross-pollination, and pronounced seed heteromorphism. These features ensure the formation of persistent soil “seed banks” that support long-term population recovery even after mechanical or agronomic interventions. In addition, the considerable genetic variability of the species promotes local adaptation to changing climatic and anthropogenic factors, complicating control efforts across regions. It was emphasized that the expansion of ragweed in Europe and Asia leads to reduced crop yields, displacement of native species, and ecosystem degradation. Losses in the agricultural sector are associated with both direct decreases in the productivity of maize, sunflower, soybean, and other crops, and with increasing costs of herbicide application. However, chemical control is complicated by the development of resistance to major groups of herbicides. This underlines the relevance of integrated weed management approaches, that combine agronomic practices (crop rotation, optimization of sowing density, cultivation of competitive crops), biological control (entomophages, phytopathogens, microbial preparations), chemical methods, and environmentally safe technologies. A promising direction is the use of modern geographic information systems, remote sensing methods, and mathematical modeling to monitor the spread of A. artemisiifolia and predict its invasion dynamics under climate change. Such an approach makes it possible to identify priority control areas and effectively allocate resources. Further research should focus on improving adaptive integrated management systems for ragweed populations, assessing the long-term consequences of its invasion for biodiversity and human health, and developing ecologically oriented models of sustainable land use.